Rancang Bangun Plotter 2D Mini Berbasis Arduino Nano - M.Ihsan Reza; Noptin Harpawi (ABEC Indonesia, 2021)
Abstract CNC (Computer Numerical Control) is a machine tool automation system that is operated by abstract programmed commands and a computer-driven control machine that produces very high precision. With this tool, for problems in making logo printing, which previously could be said to be a fairly expensive business because the equipment costs were high enough, it made it difficult for home industries and new entrepreneurs to enter the business. Testing data retrieval using different textures such as plastic, paper, cloth, and leather obtained quite satisfactory results with a percentage of 90%, Thickness testing on objects that require the height of the pen position to be adjusted according to the upper surface of the object in this experiment, the size is not a problem. The imaging process saw success at 89%. in different types affect the results of the drawing, especially on the cloth using the type of pen having a rough eye and a diameter that is too small like a twin pen, the estimated success is 65% on leather and cloth. If you use a pen with a diameter of 1.0mm-1.2mm, the success rate is 90%, but if the pen is inked with a marker it causes the ink to spread everywhere, making it 80% successful. If on paper and leather the results are 90% with any type of pen.